Factors influencing client recall of contraceptive counseling at community-based distribution events in Kinshasa, Democratic Republic of the Congo - Rebecca E. Rosenberg; Pierre Z. Akilimali; Julie H. Hernandez; Jane T. Bertrand (BMC, 2021)
Abstract Background Clients must recall information from contraceptive counseling sessions to properly use their chosen method. Client recall in community-based settings is challenging given the public nature of these events and the presence of many potential distractions. Understanding the factors that influence client recall during community-based distribution events can guide future training of providers to improve proper use of contraceptive methods and client satisfaction. Methods This cross-sectional study employed a convenience sample of 957 women ages 15-49 old who sought contraceptive services from community-based contraceptive distribution events in Kinshasa, Democratic Republic of the Congo, known as Lelo PF. Recall scores were developed by matching direct observations with client exit interviews. The association between recall and client characteristics, provider characteristics and an index for the quality of the provider-client interaction were tested using multivariate linear regression. Results The average recall score was 67.6%. Recall scores were higher among clients who accepted methods with simpler administration procedures, such as CycleBeads (81.3%), compared to methods requiring more medically advanced administration procedures, such as DMPA-SC (56.6%) and Implanon-NXT (62.1%). This relationship held even after controlling for amount of information each client received. Status as a first-time user was associated with a 5.8 percentage point decrease in recall score (p = 0.002). Time since the provider's initial family planning training and clients' perception of the provider-client interaction were associated with higher client recall scores. Conclusion Results of this study suggest that to improve client recall at Lelo PF events, future provider training should focus on how to deliver clear, specific information to clients, making sure clients feel at ease during the counseling session, and treating clients with respect. First-time family planning users and clients who select methods with more medically advanced administration procedures may require extra attention during the consultation to ensure they are able understand and remember the information. Results suggest that providers who have been offering services longer may be more effective in conveying information in a way that clients can remember. Program managers should consider requesting input from experienced providers to improve training sessions.